BALANCE SHEET ANALYSIS OF PINE RESIN RESOURCES IN SOUTH SULAWESI - makkarennu makkarennu; Nurul Ishneini S; Supratman (Jurnal Belantara, 2026)
Pine resin is a valuable non-timber forest product that serves as an important source of income for communities residing near forested areas. Despite ongoing extraction and utilization, limited information exists regarding the quantitative balance of this natural resource from initial reserves to final stocks. This study aims to clearly evaluate the physical and monetary balance of pine resin resources in a selected village in Gowa District South Sulawesi. Data were collected through interviews, field observations, and literature review. A purposive sampling method was employed to select 20 active pine resin tappers as respondents. The physical balance was determined by calculating the initial stock, annual additions, and the final stock, while the monetary balance was derived by converting final physical stock into monetary value. The results show that the final physical stock of pine resin reaches 23.584 kg per year with a corresponding monetary value of IDR 1,420,348,288. The findings clearly indicate that pine resin resources experience continuous annual depreciation when regeneration through pine tree planting is absent. These results emphasize the urgent need for sustainable pine resin management strategies to maintain resource availability and long-term community livelihoods.